Poly(vinylidene fluoride)/halloysite nanotubes nanocomposites: The structures, properties, and tensile fracture behaviors. Issue 1 (18th July 2012) - Tang, Xue‐Gang; Hou, Meng; Zou, Jin; Truss, Rowan
Abstract Poly(vinylidene fluoride)/halloysite nanotubes (HNTs) nanocomposites with good dispersion were prepared. The effect of HNTs on the crystalline structure, dynamic rheological properties, dynamic mechanical properties, and tensile properties was investigated. Results showed that at low concentration, the effect of HNTs on the modulus was minor. However, at high concentration, improvement of the modulus can be observed. The tensile fracture behaviors were investigated, which showed that the addition of HNTs changed the fracture mode. When the concentration of HNTs was 20 phr, a fracture mode change from microductility/brittle to brittle/fibrillation occurred. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013